Asertive Training As Character Education To Reduce Smoking Behavior Among Student In Industrial Revolution Era 4.0 - Siregar, Dina Mariana (International Journal of Applied Guidance and Counseling, 2020)
Smoking is a form of delinquency at a moderate level, but can provide a tendency for adolescents to lead to more severe delinquency. According to the global youth tobacco survey (gyts) in 2014 the proportion of the age of first attempting to smoke in men aged 10-11 years was 26.7%, aged 12-13 years 43.4%, aged 14-15 years 7.3%. These data address the majority of men who smoke for the first time at the age of 12-13 years. The proportion of women who first tried smoking was 10-11 years old 18%, aged 12-13 years 4%, aged 14-15 years 21.5%. The occurrence of smoking behavior on the subject is caused by the process of modeling from the social environment, namely by seeing and observing the smoking behavior of his friends then the subject tries to imitate and follow the smoking behavior of his friends psychological intervention indeed to shape the character of students in the era of the industrial revolution 4.0 which is able to reduce smoking behavior in students as a form of preventive measures. Assertive training aims to shape the personality of students so that they are better able to reject the invitation of friends or others to take actions that refer to smoking behavior. This training is expected to be able to change the mindset of students who tend to imitate and copy the behavior of their peers. Assertive training also affects the personality of students who are still lacking the courage to refuse politely and without harming others.